2008
DOI: 10.1086/524679
|View full text |Cite
|
Sign up to set email alerts
|

On the X‐Ray Light Curve, Pulsed‐Radio Emission, and Spin Frequency Evolution of the Transient Anomalous X‐Ray Pulsar XTE J1810−197 during Its X‐Ray Outburst

Abstract: We show that (1) the long-term X-ray outburst light curve of the transient AXP XTE J1810À197 can be accounted for by a fallback disk that is evolving toward quiescence through a disk instability after having been heated by a soft gamma-ray burst, (2) the spin-frequency evolution of this source in the same period can also be explained by the disk torque acting on the magnetosphere of the neutron star, and (3) most significantly, recently observed pulsed-radio emission from this source coincides with the epoch o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 33 publications
(56 reference statements)
1
52
0
Order By: Relevance
“…We note that, in the present work, we have also refined the model parameters obtained by Ertan & Erkut (2008) for XTE J1810−197 considering the newly reported last three data points of this source (Bernardini et al 2009). Illustrative model curves given in Ertan & Erkut (2008) can produce the 2-10 keV absorbed data 1 for a particular α cold .…”
Section: Parametermentioning
confidence: 77%
See 3 more Smart Citations
“…We note that, in the present work, we have also refined the model parameters obtained by Ertan & Erkut (2008) for XTE J1810−197 considering the newly reported last three data points of this source (Bernardini et al 2009). Illustrative model curves given in Ertan & Erkut (2008) can produce the 2-10 keV absorbed data 1 for a particular α cold .…”
Section: Parametermentioning
confidence: 77%
“…The X-ray outburst light curve of this source showed a different decay morphology than those of persistent sources (Ibrahim et al 2004;Bernardini et al 2009). By means of model fits to the X-ray enhancement data, Ertan & Erkut (2008) concluded that this difference could be due to a viscous disk instability (see, e.g., Lasota 2001 for a review of the disk instability model (DIM)) in the fallback disks at a critical temperature in the ∼1000-2000 K range. The fallback disks around AXPs are expected to have similar chemical compositions.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…They have been developed in a series of connected, selfconsistent ideas by means of detailed quantitative models (Ekşi & Alpar 2003;Ertan & Alpar 2003;Ertan & Cheng 2004;Ertan et al , 2007Ertan et al , 2009Ertan & Çalışkan 2006;Ertan & Erkut 2008). These models do not explain the super-Eddington bursts.…”
Section: Introductionmentioning
confidence: 99%